ЎҚУВЧИЛАРНИ ЗАРАРЛИ АХБОРОТЛАРДАН ҲИМОЯ ҚИЛИШНИНГ ҲУҚУҚИЙ АСОСЛАРИ - Жамолдинова, О. (SCIENCE and SOCIETY, 2020)
The article highlights the most important problems of public education to protect students from information that harms their health, this issue is the main aim of the law of the Republic of Uzbekistan “About protecting children from detrimental to their health information”.
Keywords: conception of continuous education; information security; information environment; informational product; guarantees for receiving information; rights of the child; governmental and non- governmental institutions